Two-Dimensional Nanoarchitectures for Lithium Storage - Liu, Jiehua; Liu, Xue-Wei (Advanced materials (Weinheim), 2012)
Two dimensional nanoarchitectures are of great interest in lithium storage for energy‐storage devices, in particular lithium‐ion batteries, due to its shortened paths for fast lithium ion diffusion and large exposed surface offering more lithium‐insertion channels. Their competitive lithium‐storage features provide huge potentials to develop next‐generation high‐performance lithium‐ion batteries. This review is devoted to the recent progress in the fabrication of innovative 2D structures with various synthetic strategies and their applications for lithium storage in lithium‐ion batteries. These 2D architectures are categorized into six styles, i.e., nanoporous nanosheets, ultrathin nanosheets, flower‐like structures assembled by nanosheets, sandwich‐like nanosheets, corrugated nanosheets, and nanosheets with specific facets. Based on the lithium‐storage manner, we further summerized their electrochemical performance for lithium storage with four classified themes including surface Li storage, zero or low‐strain Li storage, volume‐variation Li storage and synergic‐effect Li storage. Finally, the outlook and perspective on 2D lithium‐storage materials is concisely provided. Inspired by nature, this review is devoted to the recent progress in the fabrication of novel 2D structures and their lithium‐storage performance. We herein present a comprehensive overview of six kinds of novel 2D nanostructures in view of their structures obtained with various synthetic strategies. Moreover, the lithium‐storage capabilities of 2D architectures are categorized by four themes based on the Li‐insertion method.